2017
DOI: 10.1007/s00244-017-0412-y
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Cadmium and Cotinine Levels and Hair Mercury Levels in Czech Children and Their Mothers Within the Framework of the COPHES/DEMOCOPHES Projects

Abstract: The COPHES/DEMOCOPHES twin project was performed in 2011-2012 in 17 European countries to harmonize all steps of the human biomonitoring survey. Urinary cadmium, cotinine, phthalate metabolites, and hair mercury were measured in children (N = 120, 6-11 years) and their mothers of reproductive age, living in urban or rural areas. Cadmium in mothers' and children's urine was detected at a geometric mean (GM) concentration 0.227 and 0.109 μg/L, respectively; 95th percentile (P95) was 0.655 and 0.280 μg/L in mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
6
1
1
Order By: Relevance
“…Levels observed in this study were similar to those found in previous Spanish studies conducted on children, such as in 4-year-old children from Menorca [29] and from Granada [8], both populations with a geometric mean (GM) of 1.0 µg/g and around 50% of the children with levels above the EPA recommendations. On comparing with international studies, levels observed in this study were much higher than those observed in other populations from North or East Europe, such as 6-11-year-old children from the Czech Republic (geometric mean = 0.098 µg/g) [30], Denmark (geometric mean = 0.326 µg/g) [31] or Germany (geometric mean = 0.055 µg/g). Other European studies conducted in Mediterranean regions found Hg concentrations that were higher than in North Europe, but still lower than in our study, such as in children aged 7-9 years from Italy (mean = 0.88 µg/g) [32] or 11-12-year-old children from Greece (GM: 0.30-0.44 µg/g, depending of the location) [33].…”
Section: Discussioncontrasting
confidence: 55%
“…Levels observed in this study were similar to those found in previous Spanish studies conducted on children, such as in 4-year-old children from Menorca [29] and from Granada [8], both populations with a geometric mean (GM) of 1.0 µg/g and around 50% of the children with levels above the EPA recommendations. On comparing with international studies, levels observed in this study were much higher than those observed in other populations from North or East Europe, such as 6-11-year-old children from the Czech Republic (geometric mean = 0.098 µg/g) [30], Denmark (geometric mean = 0.326 µg/g) [31] or Germany (geometric mean = 0.055 µg/g). Other European studies conducted in Mediterranean regions found Hg concentrations that were higher than in North Europe, but still lower than in our study, such as in children aged 7-9 years from Italy (mean = 0.88 µg/g) [32] or 11-12-year-old children from Greece (GM: 0.30-0.44 µg/g, depending of the location) [33].…”
Section: Discussioncontrasting
confidence: 55%
“…27,51 Hg concentration in the mother's hair was higher than in children. 52 Its level increased in accordance with the number of dental amalgam fillings in the children, as well as the consumption of marine and fish products. 53 On average, the levels of Hg in the body of the screened persons did not exceed the recommended values.…”
Section: Mercury Levels In Blood and Urinementioning
confidence: 95%
“…Biomonitoring of the state of maternal and child health conducted in the framework of the COPHES/ DEMOCOPHES project reported that the Hg concentration in the urine of mothers living in the city was higher than in rural women . Hg concentration in the mother’s hair was higher than in children . Its level increased in accordance with the number of dental amalgam fillings in the children, as well as the consumption of marine and fish products .…”
Section: Insights On the Environmental Indices Of Exposure Of Mercurymentioning
confidence: 99%
“…The role of SHS exposure in urinary cadmium levels was also not conclusive. As an example, similar cadmium concentrations were found in children exposed and non-exposed to SHS, without clear correlations with urinary cotinine [46,115]. Conversely, Sánchez-Rodríguez et al found that urinary cadmium levels slightly decreased in 83 adults after the implementation of a restrictive anti-smoking legislation, ranging from 0.17 (0.11–0.29) μg/g cr before the smoking ban to 0.10 (0.06–0.22) μg/g cr one year after the law implementation.…”
Section: Tobacco-related Biomarkersmentioning
confidence: 91%
“…The typical urinary cotinine cutoff value is 30 ng/mL. Urinary cotinine concentrations usually range from 34.5 to 489 ng/mL for smokers [46,47], from 0.25 to 30 ng/mL for SHS exposed nonsmokers [22,36,42,45,46,48,49,50], up to 5 ng/mL for THS exposed nonsmokers [41,43,44] and around 0.88 ng/mL in non-exposed nonsmokers [43]. Nevertheless, acute exposure to SHS can raise urinary cotinine concentrations to levels similar to those reported in smokers’ concentrations.…”
Section: Tobacco-specific Biomarkersmentioning
confidence: 99%